Who Is Exposed to News? It Depends on How You Measure: Examining Self-Reported Versus Behavioral News Exposure Measures. (October 2020) - Vraga, Emily K.; Tully, Melissa
Despite the importance of news exposure to political outcomes, news consumption is notoriously difficult to measure, and misreporting news exposure is common. In this study, we compare participants' news behaviors measured on a news aggregator website with their self-reported story selection immediately after exposure. We find that both individual and contextual characteristics—especially the presence of political cues in news headlines—influence reporting of news story selection. As a result, the news audience profiles differ using self-reported versus behavioral measures, creating two different pictures of news exposure. More attention is needed to improve news measurement strategies to address misreporting and to improve the accuracy of news audience profiles.